2016
DOI: 10.1111/vop.12432
|View full text |Cite
|
Sign up to set email alerts
|

Heat‐shock protein 70 expression in the equine cornea

Abstract: These findings suggest the expression of HSP70 is induced in the normal equine cornea during re-epithelialization and may be altered in sterile keratopathies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…HSPs are ubiquitous proteins that serve critical functions in the response to biotic and abiotic stresses (24). A previous study by Peterson et al (25) demonstrated that HSPs promote epithelial wound healing in various tissues, whereas reduced HSP70 expression may potentially prolong the healing process in the pathologic cornea of animals. Certain HSP70s, including molecular chaperones, serve a pivotal function in various biological processes, including the regulation of protein folding, interactions between proteins and translocation and degradation across membranes (26).…”
Section: Discussionmentioning
confidence: 97%
“…HSPs are ubiquitous proteins that serve critical functions in the response to biotic and abiotic stresses (24). A previous study by Peterson et al (25) demonstrated that HSPs promote epithelial wound healing in various tissues, whereas reduced HSP70 expression may potentially prolong the healing process in the pathologic cornea of animals. Certain HSP70s, including molecular chaperones, serve a pivotal function in various biological processes, including the regulation of protein folding, interactions between proteins and translocation and degradation across membranes (26).…”
Section: Discussionmentioning
confidence: 97%
“…In the horse, two HSP90 isoforms (HSP90α and HSP90β) have been described (Pratt, 1997), encoded by the HSP90AB1 gene (César Cortés‐González, Ramírez‐González, Ariza, & Bobadilla, 2008). This gene is expressed in cerebellum, testis, embryo, cornea, blood and muscle (Coleman, Zeng, Hestand, Liu, & Macleod, 2013; Peterson, Driskell, Wilkie, Premanandan, & Hamor, 2017; Avenatti, McKeever, Horohov, & Malinowski, 2018).…”
Section: Introductionmentioning
confidence: 99%